Analysis Discrimination and Low Understanding Right Patient Guarantee National Health on Service House Sick - Aris Prio Agus Santoso; Fauzan Nur Abadi; Firmansyah Nur Arifin; Rojali Koiri Najib (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Study This aim analyze phenomenon discrimination to patient Guarantee National Health Insurance (JKN) and limitations knowledge patient about his rights . Space scope study service - focused House sick in Indonesia with review aspect legal , social , and access health . The method used is study normative with approach studies literature , through secondary data review from the Indonesian Ombudsman, BPJS Watch, Riskesdas 2018, and various publication academic . Data includes surveys and reports national which shows more of 21% of JKN patients experienced treatment discriminatory , time wait an average of 3–5 hours, and low level knowledge rights (47%). Findings confirm existence discrimination systemic which has implications for injustice structural , reinforced by gaps information patient . Analysis test literature support the need reform service and socialization right patient . This study underscores the importance of improving both the dissemination of information about patients' rights and the responsiveness of healthcare services, to ensure equitable and just treatment for all individuals under the JKN program.